Effect of Multimedia Instructional Approach on English Writing Performance of Pre-service Technical Teachers in South-Western Nigeria - Olowoyeye, Cyril Abioye Charles; Deji-Afuye, Oladuni Olufuns; Aladesusi, Gboyega Ayodeji (ASEAN Journal of Educational Research and Technology, 2022)
This study examined the Effect of the Multimedia Instructional Approach (MIA) on the English writing performance of pre-service technical teachers in Southwestern Nigeria. The study adopted a quasi-experimental design of the pre-test post-test non-equivalent control group design to compare the performance of students who are exposed to MIA and those that are not. The population for this study consists of the college of education students located in the South-West geo-political zone of Nigeria. Four Colleges of Education were purposively sampled out of the 7 state-owned colleges of education from southwestern Nigeria.  The following research instruments were adopted for the study: English Writing Performance Tests (EWPT) set A; EWPT Set B; and Multimedia Instructional Software Package. The reliability coefficient of the instruments was calculated at a reliability coefficient of 0.82. Mean, standard deviation, and analysis of covariance (ANCOVA) were used for data analyses at 0.05 level of significance. The findings of the study revealed that MIA was effective for teaching English language writing and there is no significant difference between males and females in the English writing performance of the pre-service technical teachers taught through MIA. This study concluded that MIA for English writing is an important variable because it is better to predict students’ writing performance in the English Language than the conventional method of teaching.